Molecular identification of surface protein antigens of Campylobacter jejuni. - Logan, S M (1983)
The technique of immunoblotting was used to identify the surface protein antigens of Campylobacter jejuni. Polyclonal antisera were raised in rabbits to formalinized cells of a typical human fecal isolate, C. jejuni VC74. Surface components were separated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Fractions analyzed included whole cell lysates, sarcosinate-extracted outer membranes, released outer membrane blebs (fragments), isolated flagella, 0.2 M glycine-hydrochloride (pH 2.2) extract, saline extract, and material released by osmotic shocking. The ability of the antisera to recognize corresponding antigens on other strains of thermophilic campylobacters and Campylobacter fetus was also determined. The results demonstrated that heat-labile antigenic specificity was conferred on C. jejuni VC74 by an outer membrane protein with an approximate molecular weight of 92,500. Both the major outer membrane protein and the flagella were immunogenic but did not confer either strain or species serospecificity on the strains tested. Another major antigen on thermophilic campylobacter cells was a surface protein with an approximate molecular weight of 31,000. This common antigen was preferentially removed by glycine extraction but was not detectable in outer membrane prepared by sarcosinate extraction.